THE INFLUENCE OF BRAND EQUITY, QUALITY OF SERVICE, LOYALTY AND WORD OF MOUTH ON PURCHASE DECISION OF XPANDER CAR - AlQadri Ilham; Otto Randa Payangan; Andi Nur Bau Massepe (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
This study aims to determine and analyze the effect of marketing strategies partially influencing the purchase decision of a Mitsubishi Xpander car. This writing uses a random sampling technique, used a sample of 130 respondents. To apply these objectives, data collection techniques through questionnaires are used, with multiple linear regression analysis, and hypothesis testing. Based on the results of multiple linear regression analysis, it shows that the variables Brand equity, Service Quality, Loyalty, Word of Mouth significantly affect the purchasing decision of the Mitsubishi Xpander Car. Thus, there is a partially influencing marketing strategy on the purchasing decision of the Mitsubishi Xpander Car.